Dynamic Slimmable Network for Speech Separation - Elminshawi, Mohamed; Chetupalli, Srikanth Raj; Habets, Emanuël (IEEE Signal Processing Letters, 2024)
Neural networks for speech separation generally exhibit high computational costs and large memory footprints. Moreover, typical separation networks have a fixed computational graph that processes all input frames at a uniform computational cost, even though intensive processing may not be necessary for frames containing silence or a single active speaker. Addressing this computational inefficiency is especially crucial when these networks are deployed on resource-constrained devices. In this letter, we propose a dynamic slimmable network for speech separation that mitigates the computational inefficiency of existing networks. We introduce slimmable layers with a gating mechanism that can adapt their computational complexity based on the input characteristics. As an example, we propose to use the slimmable layers in the intra-chunk blocks of a dual-path structure-based network to facilitate adaptation based on the local characteristics of the input signal. Experimental evaluation on simulated two-speaker mixtures from the WSJ0-2mix dataset demonstrates that the proposed method substantially reduces the computational cost while maintaining comparable performance to fully utilized static networks.
CRIS-Team Scopus Importer:2024-10-25
Keywords: conditional computation; dynamic slimmable network; Speech separation; transformer architecture

Noise-Robust Adaptation Control for Supervised Acoustic System Identification Exploiting a Noise Dictionary - Haubner, Thomas; Brendel, Andreas; Elminshawi, Mohamed; Kellermann, Walter (IEEE International Conference on Acoustic, Speech and Signal Processing (ICASSP), 2021)
Keywords: System Identification; Adaptation Control; Nonnegative Matrix Factorization; Acoustic Echo Cancellation

Speaker Verification in Multi-Speaker Environments Using Temporal Feature Fusion - Aloradi, Ahmad; Mack, Wolfgang; Elminshawi, Mohamed; Habets, Emanuël (2022 30TH EUROPEAN SIGNAL PROCESSING CONFERENCE (EUSIPCO 2022), 2022)
CRIS-Team WoS Importer:2023-02-24